Legal and Socio-Ethical Issues in Punishment - OKON, ETIM E. (2013)
The purpose of this paper is to reflect on the legal and socio-ethical implications of punishment. We have reviewed existing literatures on punishment with a view to establish a synthesis of scholarly opinions on punishment. It is appropriate for civil authorities to be properly educated on the functions of punishment. Public policy on punishment should have social dimension. Punishment should be seen as an aspect of social engineering. The study has strongly recommended that the purpose of punishment should ultimately be the reformation of offenders